P–340 Novel non-invasive diagnostic options for endometriosis - based on glycome analysis. (6th August 2021) - Kovacs, Z; Adamczyk, B; Reidy, F; McAuliffe, F M; Rudd, P M; Wingfield, M; Glover, L; Saldova, R
Abstract: Study question: Could glycosylation changes on serum and/or urine glycoproteins be suitable biomarkers for the non-invasive diagnosis of endometriosis? Summary answer: The glycosylation pattern on serum and urine glycoproteins differed significantly in endometriosis patients compared to controls, suggesting a novel role as biomarkers of the disease. What is known already: There is little published on endometriosis and glycosylation, and most of the studies are conducted with tissue or peritoneal fluid samples, collected by invasive means. An Iraqi study draws attention to the importance of serum sialylation, which is dramatically changed in endometriosis patients after zoladex therapy, indicating that changes in serum sialylation may be a new biomarker of the disease. While glycosylation of urine in endometriosis has not been studied so far, in a study of endometrial cancer, the urinary level of two glycoproteins was significantly increased in the patients compared to the control group. Study design, size, duration: This was a prospective study. In this basic research project, serum and urine samples were collected for glycome analysis in women with and without endometriosis, as diagnosed at laparoscopy. Glycated haemoglobin (HbA1c), fasting glucose levels as well as hormone levels were also collected from the patients to link our glycomic findings with metabolic and hormone profiles. The study was approved by the Research and Ethics Committee of the National Maternity Hospital, Dublin (EC19.2018). Participants/materials, setting, methods: Samples from 24 cases of endometriosis (patients without previous anti-inflammatory or hormonal therapy, endometriosis was confirmed by laparoscopy) and 27 control patients (patients without endometriosis) were processed to analyse N-glycans (total serum), urine glycoproteins, and IgG. The pre-processed, PNGase F-digested serum and urine samples were labelled with fluorescent tag and then analysed by mass spectrometry, ultra-performance liquid chromatography (UPLC) in combination with exoglycosidase digestions and Glycostore (https://glycostore.org/). Main results and the role of chance: Glycosylation on total serum and urine glycoproteins and IgG was investigated and differed in endometriosis compared to controls. The N-glycome from the total glycoproteins in serum and urine was also different. The proportion of the galactosylation and sialylation differed between urine and serum IgG and these alterations have an impact on the IgG function. Our preliminary data indicate, that there is an increase in alpha 2–3 sialylation, galactosylation, and fucosylation on urine glycans from endometriosis patients compared to the control pool. Urine is a good source of biomarkers as it can be collected non-invasively. Our group is the first to have developed a protocol for the recovery of N-glycans in urine and to have identified the total N-glycome in urine. The urine N-glycome contains mostly complex N-glycans and also some oligomannosylated and hybrid glycans. Our results may lead to non-invasive biomarkers for the diagnosis of endometriosis and the monitoring of the disease. Limitations, reasons for caution: The number of participants involved in this basic research is low but this is a pilot study. A larger, validation study, is warranted in the future. Furthermore, the follow-up of treated patients also would be an interesting field of research. Wider implications of the findings: Glycomics may be a potent source of biomarkers of endometriosis, with a number of glyco-biomarkers already approved by the FDA. Endometriosis-associated glycomic profiles from serum and/or urine glycoproteins may represent viable targets for development of innovative non-invasive or minimally invasive diagnostics in this debilitating disease. Trial registration number: Not applicable